2015
DOI: 10.1007/s11738-015-1935-3
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical responses of sugarcane to oxidative stress induced by water deficit and paraquat

Abstract: Physiological and biochemical responses to oxidative stress induced by paraquat or water deficit were examined in this study with respect to photoinhibition, stomatal conductance, photosynthetic pigments, organic solutes, and antioxidant enzymes, aiming at a better understanding of the defense networks connected with antioxidant agents in sugarcane and also to identify cultivars more tolerant to such stress conditions. In the droughtinduced experiment, the plants were exposed to 15 days without irrigation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 53 publications
6
37
0
1
Order By: Relevance
“…The superoxide dismutase (SOD) activity plays the first line of enzymatic ROS scavenging, catalyzing the conversion of O2- into H 2 O 2 within the cell. In sugarcane, SOD activity is genotype-dependent and is also modulated by water stress (Hemaprabha et al, 2004; Jain et al, 2015; Sales et al, 2015; dos Santos et al, 2015; dos Santos and de Almeida Silva, 2015). Moreover, (Jangpromma et al, 2012) showed that sugarcane cultivars classified as drought-tolerant exhibit higher levels of SOD activity under water deficit conditions.…”
Section: Ros Accumulation and Antioxidant Activitymentioning
confidence: 99%
“…The superoxide dismutase (SOD) activity plays the first line of enzymatic ROS scavenging, catalyzing the conversion of O2- into H 2 O 2 within the cell. In sugarcane, SOD activity is genotype-dependent and is also modulated by water stress (Hemaprabha et al, 2004; Jain et al, 2015; Sales et al, 2015; dos Santos et al, 2015; dos Santos and de Almeida Silva, 2015). Moreover, (Jangpromma et al, 2012) showed that sugarcane cultivars classified as drought-tolerant exhibit higher levels of SOD activity under water deficit conditions.…”
Section: Ros Accumulation and Antioxidant Activitymentioning
confidence: 99%
“…In terms of SOD enzyme activity in roots and leaves of maize seedlings; there was the maximum increase in Danona for Atrazine (Zhang et al, 2014;Griboff et al, 2014;Li et al, 2012;Santos & Silva, 2015;Kraus et al, 1995;Chen et al, 2016;Jiang et al, 2016) and the maximum decrease in roots of Danona and in leaves of Saccharata for metolachlor (Xie et al, 2014;Stajner et al, 2003;Wang & Zhou, 2006). Antioxidant system plays a crucial role for protecting cellular compounds from damages of reactive oxygen species produced under stress.…”
Section: Discussionmentioning
confidence: 99%
“…This is because SOD plays a role in eradication of superoxide radical from chloroplasts and superoxide radical is converted into H2O2. Herbicide toxicity occurs as a result of SOD activation substantially increasing in antioxidant system (Santos & Silva, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance between SOD and APX or CAT activities in cells is crucial for determining the steady-state level of H 2 O 2 and superoxide radicals [35]. SOD acts as the first line of defense converting O 2 -into H 2 O 2 , APX, and CAT, and then detoxifying H 2 O 2 into O 2 and MDA [12].…”
Section: Oxidative Products and Antioxidant Enzyme Activitiesmentioning
confidence: 99%